2013
DOI: 10.1037/a0031226
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-basal ganglia and cortico-cerebellar circuits in Parkinson's disease: Pathophysiology or compensation?

Abstract: The basal ganglia and the cerebellum are anatomically and functionally linked to the cerebral cortex through a series of well-established circuits. The disruption of dopaminergic projections in Parkinson's disease (PD) leads to an imbalance within these circuits, leading to motor and cognitive symptoms. The cortico-cerebellar (CC) network has often been viewed as a compensatory network, helping the dysfunction of the cortico-basal ganglia (CBG) circuits in PD. However, evidence for this compensatory role is sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 164 publications
(224 reference statements)
1
59
1
Order By: Relevance
“…It has been reported in non-demented PD patients that lowered regional cerebral metabolic rates in the occipital area correlate with the motor dysfunction (Bohnen et al, 1999) We also previously reported lower regional cerebral metabolic rates for glucose in the occipital area accompanied by dopaminergic availability in the striatum, along with motor dysfunction in non-demented PD patients (Nagano-Saito et al, 2004) Simultaneously, cerebellar activity is likely to contribute to pathophysiological change underlying PD (Martinu and Monchi, 2013) Thus, the reduced activation in the occipital area and cerebellum may reflect remote effects of the progress of the disease on dopamine projections in the striatum. However, they might also reflect a learning effect with reduction of visual attention and motor effort at Time 2.…”
Section: Discussionmentioning
confidence: 80%
“…It has been reported in non-demented PD patients that lowered regional cerebral metabolic rates in the occipital area correlate with the motor dysfunction (Bohnen et al, 1999) We also previously reported lower regional cerebral metabolic rates for glucose in the occipital area accompanied by dopaminergic availability in the striatum, along with motor dysfunction in non-demented PD patients (Nagano-Saito et al, 2004) Simultaneously, cerebellar activity is likely to contribute to pathophysiological change underlying PD (Martinu and Monchi, 2013) Thus, the reduced activation in the occipital area and cerebellum may reflect remote effects of the progress of the disease on dopamine projections in the striatum. However, they might also reflect a learning effect with reduction of visual attention and motor effort at Time 2.…”
Section: Discussionmentioning
confidence: 80%
“…This can be interpreted as a seed specific PD-related FC decrease, i.e., that the FC between the anterior right dlPFC seed and the left lateral cerebellum shows a significantly stronger decrease in PD than between the posterior right dlPFC cluster and this cerebellar region. In PD, several alterations in the functional activation and connectivity of the cerebellum have been reported related to various motor and cognitive symptoms of the disease (see Martinu and Monchi, 2013; Wu and Hallett, 2013 for reviews). The cerebellum is reciprocally connected to the prefrontal cortex via the cerebello-thalamo-cortical circuit.…”
Section: Discussionmentioning
confidence: 99%
“…However, while our review does not especially addresses a neurological disease (e.g. Parkinson disease), we would like to refer to other reviews which deal with cognitive dysfunctions and the resulting motor limitations (Grabli et al, 2012;Heremans et al, 2013;Hirano et al, 2012;Iansek et al, 2013;Lindenbach and Bishop, 2013;Martinu and Monchi, 2013;Ricciardi et al, 2014;Silbert and Kaye, 2010;Vercruysse et al, 2014). Interestingly, exercise treatments are helpful to improve cognitive and motor symptoms in Parkinson disease (Ahlskog, 2011;Murray et al, 2014;Petzinger et al, 2013).…”
Section: Neurological Pathologymentioning
confidence: 96%